STRATEGI PERENCANAAN IMPLEMENTASI SISTEM INFORMASI MANAJEMEN PENGOLAHAN DATA PENANGKAPAN IKAN DI KEMENTERIAN KELAUTAN DAN PERIKANAN - Pandu Saptoriantoro; . Mustaruddin; John Haluan (Bogor Agricultural University, 2017)
ABSTRACTMinistry of Marine Affairs and Fisheries Republic of Indonesia has a management information system on data processing of fishing surveillance. The information system can be useful if the system is works successfully. This research aim to formulate a strategic plan for the successful implementation of management information systems of data processing fisheries resources surveillance. Elements of the system on strategy was condected by using interpretative structural modeling (ISM), which is a strategic planning technique. The results show for the implementation of the model, there are seven elements of the system that need to be considered. Seven elements of the system with each sub element key, namely Directorat General PSDKP as affected sectors, support policies / regulations, conflict of interest between units echelon 1, up date data licensing continuity and fixed information technology (IT) expert. The implementation of fisheries resources surveillance program by IT based, mostly regional operators started to use information systems surveillance of fishery resources, increased access to data and information across echelons in MMAF and involvement MMAF as agencies involved in the success of the program.Keywords: Directorate of fisheries resources surveillance and management, information system, implementing strategy, ISMABSTRAKKementerian Kelautan dan Perikanan memiliki sistem informasi manajemen pengolahan data pengawasan penangkapan ikan. Sistem informasi tersebut berguna jika dalam implementasi sistem berhasil dengan baik. Penelitian ini bertujuan merumuskan rencana strategis untuk keberhasilan implementasi sistem informasi manajemen pengolahan data pengawasan perikanan tersebut. Strategi penerapan implementasi sistem informasi dilakukan dengan teknik interpretative structural modelling (ISM). Elemen sistem pada strategi perencanaan implementasi sistem informasi, yaitu Direktorat jenderal Pengawasan Sumberdaya Kelautan dan Prikanan (PSDKP) sebagai sektor yang terpengaruh, dukungan kebijakan/peraturan, up datedata perizinan yang kontinuitas dan tenaga ahli Teknologi Informasi (IT), terlaksananya program pengawasan sumber daya perikanan berbasis IT, sebagian besar operator daerah mulai menggunakan sistem informasipengawasan sumber daya perikanan, peningkatan akses data dan informasi lintas eselon lingkup Kementerian Kelautan Perikanan (KKP) dan keterlibatan Kementerian Kelautan dan Perikanan sebagai lembaga yang terlibat dalam keberhasilan program.Kata kunci: Dit. PPSDP, Sistem Informasi, Strategi implementasi, ISM